HUBUNGAN MOTIVASI KERJA PERAWAT DENGAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN RAWAT INAP DI RUMAH SAKIT SENTRA MEDIKA CISALAK - Riya Indriani; Marini Agustin (Afiat, 2019)
Introduction nurses must have motivation in work, especially in documentation. Documentation of the nursing process includes assessment, problem identification, planning, nurse actions, then observing and evaluating the client's response to the action given and informing the information to other health workers. The results of data obtained in documenting inpatient nursing care there are completeness targets that have not been achieved. The purpose of the study was to determine the relationship between nurses' work motivation and documenting inpatient nursing care at the sentra medika cisalak hospital. Research method is descriptive correlative with cross-sectional approach. The total population is 50 respondents in the adult inpatient room. Results based on the results of the study there were 52.0% of respondents had high work motivation and 62.0% of nursing care documentation that had been done. With the value of Chi Square = 0.002 <0.05, the HA hypothesis is accepted. The conclusion is that there is a relationship between nurses' inpatient work motivation in the hospital center medica cisalak (0.6138) which means “strong”. Suggestions for nurse who have implemented nursing care documentation provided rewards / awards from superiors and audits are carried out continuously.